Promoting sustainability training in future teachers through research workshops in the University Ecological Garden - Lourdes Aragón; Juan Casanova Correa (Problemy Wczesnej Edukacji)
The current planetary crisis and the changes in the Spanish curriculum of Early Childhood Education require teacher training that enables future teachers to respond to these situations. This paper describes a constructivist teaching-learning sequence framed within the University Ecological Garden through an enquiry-based strategy. This educational intervention was carried out with thirdyear students of the degree in Early Childhood Education at the Universidad de Cádiz (Spain). Its outcome was a science dissemination event in which research workshops related to one or several sustainable development goals were organised. The validity of using real contexts like the garden space to achieve sustainability in the curriculum and of contributing to the scientific training of future teachers for them to be able to transfer educational interventions within the framework of sustainability was verified. Future proposals for improvement for a second implementation in the classroom were analysed.